The Sea - "Morgan, Nina" (Kingfisher, London, 1994)
Focusing on the sea, this is part of a 12-volume encyclopaedia which aims to reflect the concerns of the National Curriculum. The book explores the world's oceans, waves and tides, life under water and at the water's edge, the sea's rich resources, and the need to protect them.